Typological Analysis and Development of District Area Based on Potential Sectors in Pasaman Regency, West Sumatera Province, Indonesia - Deop Darius; Abd Jamal; Putri Bintusy Syathi (International Journal of Business, Economics, and Social Development, 2021)
The decentralization of Indonesia allowed the development in the regency level to improve to the highest level. However, the impact can only be maximized by utilizing the potential economy embodied in the regent. This study investigates the development of the Pasaman Regency by analyzing the potential sector and the stage development of the sector. Therefore, this study uses mixed research methods with explorative approaches and uses Contribution Sectors Analysis, Location Quotient Analysis model, Shift Share Analysis model, and Klassen typological analysis model, The data used is the Gross Regional Domestic Product (GRDP) of Pasaman Regency and West Sumatra Province in the period 2010 until 2019 and data on the production of the Pasaman Regency base sector in each district in 2015-2019. The result showed that the agricultural, fisheries, and forestry sectors have the largest contribution to the GRDP of Pasaman Regency which is 55.51%, then the sector that belongs to the base sector with the value of LQ>1, namely the agricultural, fisheries, and forestry sectors. The sectors that experienced a net change or shift and had a positive value and the highest level of excellence were the agricultural, fisheries, and forestry sectors of 10,718,410,000. Klassen Typology Analysis is based on the base sector, namely the agricultural, fisheries, and forestry sectors with the largest contribution to the fisheries sector so that the grouping of regions using fisheries data with the results of Panti and South Rao Districts is classified as advanced areas and Lubuk Sikaping and Mapat Tunggul Selatan districts are classified as lagging areas. There is a shift in territory caused by land transfer, changes in the profession, and accessibility. The development of district areas in Pasaman Regency through the fishery sector in the form of fish cultivation, fish feed factories, and fish processing industries is expected to improve the welfare of the community, especially sub-districts that are not classified as developed areas so that the trickle-down effect and the realization of equitable distribution